Tipping in top Auckland restaurants: does it help? - Pearson, Marcus Victor Thomas (Auckland University of Technology, 2010)
The practice of tipping in restaurants or the addition of service charges onto the bill at the end of the dining experience is the norm in many countries throughout the world. It is not normal to tip in New Zealand, however the practice has gained some acceptance, especially in Auckland’s fine-dining restaurants. This study applies a qualitative methodology to understand how the practice of tipping is managed in fine-dining restaurants. Ten restaurant owners/managers were interviewed about the phenomena of tipping and its application to their organisations. The sample was selected from 20 top, fine-dining restaurants. Excluded from the sample were hotel restaurants, as they are part of organisations that have multiple income streams. All managers spoken to said they their restaurants were dependant on their own organisation’s reputation for their business success. The findings from this research show that there are four influences on the impact of tips on an operation: teamwork, staff loyalty, good service, and restaurant organisation. Furthermore, the research suggests that tipping by New Zealanders sometimes relates to the quality of the dining experience that the customer receives. The managers emphasised the importance of good service and made every endeavour to run their operation in a professional manner providing an overall dining experience that met or exceeded customers’ expectations. This research has produced both theoretical and managerial implications. From a theoretical perspective, customers appear to tip for good service, a finding which differs from studies completed outside of New Zealand. Customers in New Zealand are willing to give a gratuity to the waiters, not because the service staff members are underpaid, but because they feel that they had a value for money experience. There are two viewpoints from a managerial perspective about tipping. Firstly, staff development and training, although often viewed as wasteful because of high staff turnover, is essential for maintaining a successful business. Tipping assisted in the retention of experienced personnel, giving longevity and continuity of service standards that are lacking in other parts of the industry. Secondly, managers should measure customer satisfaction by transparent criteria, such as customer feedback appraisals, rather than just using tips as a measurement. The key informants believed that customers tipped for good service and therefore structured their restaurant operations to deliver top service.
Keywords: Grounded theory; Tipping; Restaurant management; Hospitality; Customer service; Staff loyalty